The Influence of Price, Brand Equity and E-Commerce on Purchasing Decisions of Shure Brand Microphones at PT. Sierra Mandiri Distribusindo: The Influence of Price, Brand Equity and E-Commerce on Purchasing Decisions of Shure Brand Microphones at PT. Sierra Mandiri Distribusindo - Ferren Ferren; Vincent Wang Jaya; Sylvia Sylvia; Yollanda Yollanda; Monica Tanry; Sufika Sary (Institute of Computer Science (IOCS), 2020)
This study was conducted to analyze and examine the effect of price, brand equity, and e-commerce on purchasing decisions for Shure brand microphones at PT. Sierra Mandiri Distribusindo. This research uses quantitative methods, descriptive and causal relationships. The total population of customers of PT. Sierra Mandiri Distribusindo totaled 178 customers, using the Slovin formula obtained a sample of 124 customers. The data analysis method used is the classical assumption, multiple linear regression, and hypothesis testing. The results of the study are partially price has a significant negative effect on purchase_ decision, equity. brand. and e-commerce has a significant positive effect on purchase_ decision. Simultaneously, price, brand equity, and e-commerce have a significant effect on purchasing decisions for Shure brand microphones at PT. Sierra Mandiri Distribusindo. The amount of variation in purchasing decisions that can be explained by the variable price, brand equity, and e-commerce is 38.5%, the remaining 61.5% is influenced by other variables.